REDUCING OCCUPATIONAL RISK IN INDUSTRY BASED ON THE LABOR WEIGHT FACTOR (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article presents the theory of risk and its role in ensuring occupational safety, the methodology for quantitative assessment of possible accidents, methods for determining risk. The concept of acceptable, permissible risk, the theory of risk management, and methods for preliminary analysis of risks are discussed.